Linking transformational leadership and individual learning behavior: Role of psychological safety and uncertainty avoidance - Umer Zaman; Maha Abbasi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
The personal learning cloud is reshaping companies across industries despite the vast gap in the locus of knowledge acquisition and locus of knowledge application. While knowledge and best practices become moving targets, the modern-organizations have swiftly moved to psychological safety culture that fosters growth, innovation and individual learning. In context, transformational leadership fosters innovative behaviors and learning abilities, successful organizational transformations and effective actions for performance beyond expectations. Hence, the study aimsis to examine the impact of transformational leadership on individual learning behavior, under mediating conditions of psychological safety and moderating influence of uncertainty avoidance. Using partial least squares (PLS) based structural equation modeling (SEM) and survey of 350 telecom-employees, the results reveal that transformational leadership and individual learning behavior relationship is partially mediated by psychological safety. Alternatively, uncertainty avoidance reveals an insignificant role as a moderator. Our findings generate managerial implications for advancing individual learning cultures and guiding continuous improvements in diverse work settings. In line with the theoretical base of "too much of a good thing (TMGT) effect", our study highlights potential avenues for future research to explore the dark side of psychological safety and its counter-productive effect on workplace behaviors.
Keywords: 330; Transformational leadership; individual learning behavior; uncertainty avoidance; psychological safety; telecom sector and Pakistan